Proceso de reclutamiento, selección e inducción de personal administrativo para la mejora de la gestión de talento humano en el GADMC COLTA, período 2023. - Chagñay Lozano, Gabriela Rocio (2025)
The present research work entitled "RECRUITMENT, SELECTION AND INDUCTION PROCESS OF ADMINISTRATIVE PERSONNEL FOR THE IMPROVEMENT OF HUMAN TALENT MANAGEMENT IN THE GADMC COLTA FOR THE YEAR 2024", was carried out to carry out a situational analysis of the recruitment, selection and induction process used in the Decentralized Autonomous Municipal Government of the Canton Colta and with the information collected to propose corrective actions to improve the Human Talent Management of the same. Using a qualitative approach and with the objective of achieving the project's purposes, a 17-question questionnaire was applied, and the recruitment, selection, and induction processes of personnel were analyzed. This identified deficiencies such as the lack of transparency and the incongruence between the candidates' competencies and the positions' requirements. A non-experimental, descriptive field research design was used. The sample consisted of 20 officials selected according to the author's interest, including directors, department heads, and personnel from the Human Talent Unit, with specific profiles to address the problem. The study concludes that the current process presents several critical points, including inadequate dissemination of vacancies and an incomplete assessment of the required competencies. Therefore, the proposal resulting from the analysis includes a manual of procedures for the stages of recruitment, selection, and induction. This approach will allow GADMC Colta to have a more trained team and reduce staff turnover, facilitating more efficient management of human talent.